EXAMINING THE MORPHOLOGICAL AND CLINICAL IMPORTANCE OF NUTRIENT FORAMINA IN THE HUMAN ULNA: A CROSS-SECTIONAL STUDY - Singh, Divyanjali; Rani, Sweta; Ranjan, Rakesh (Student's Journal of Health Research Africa, 2024)
Background: Nutrient foramina in human ulna bones plays a crucial role in bone vascularization and is of significant clinical importance. Understanding their morphological characteristics and distribution is essential for various medical applications. The investigation aimed to evaluate the morphological and clinical significance of nutritional foramina in the human ulna. Methods: A total of 100 ulna bones were examined without specific age or sex determination, and NF was identified, characterized, and quantified. Data collection included measurements of bone length and foraminal index using standardized techniques. Statistical analysis was performed to assess correlations and differences between variables. Results: Nutrient foramina (NF) was identified in 85% of 100 ulna bones, primarily distributed along the diaphysis, with an average of 1.2 (±0.4) NF per bone. The mean diameter of NF was 1.5 mm (±0.3 mm). Bone length positively correlated with the foraminal index (r = 0.62, p < 0.001). Three types of foraminal indices were classified: Type I (<33.33%), Type II (33.34–66.6%), and Type III (>66.67%). No significant differences were found between left and right ulna bones or between male and female ulna bones in foraminal characteristics (p > 0.05). Ulna bones with gross pathology showed a lower NF prevalence compared to those without pathology (p = 0.021). These findings provide insights into ulna NF morphology and clinical relevance. Conclusion: The study highlights the clinical importance of ulna nutrient foramina morphology, aiding in surgical planning and bone health assessment. The positive correlation between bone length and foraminal index suggests implications for bone growth, while the classification of foraminal indices offers a framework for assessing ulna vascularization variability. Recommendations: Further research is warranted to explore the clinical significance of NF in various orthopedic conditions and to investigate potential correlations with bone health indicators.